The microbial ecology of Candida albicans strains CHN1 and SC5314 in mice. Issue 12 (17th December 2021) - Bazzi, Malak; Nawrocki, Katie; Brown, Christopher; Falkowski, Nicole; Stark, Kelsey; Huffnagle, Gary
Abstract : Strain SC5314 is the most widely studied strain of Candida albicans . Despite C. albicans being the most commonly isolated yeast from the human gastrointestinal (GI) microbiome, strain SC5314 does not stably colonize the mouse GI tract long term, even after antibiotic disruption. In contrast, strain CHN1 will stably colonize the mouse GI tract long term. Comparative genomic analysis of strain CHN1 indicates that it belongs to a different evolutionary clade of C. albicans than strain SC5314. Previous studies from our laboratory have shown that colonization by strain CHN1 causes a change in the GI bacterial microbiome of mice and predisposes them to more robust Th2 immune responses. Despite this, little is known about the GI microbial ecology of SC5314 vs. CHN1 and subsequent host responses. Using a short-term antibiotic disruption model in C57BL/6 mice, we have been able to observe significantly different colonization kinetics between these two C. albicans strains, with CHN1 establishing stable long-term colonization. In contrast, colonization by SC5314 was lower, highly variable and cage-dependent. C. albicans colonization kinetics impacted the composition of the bacterial microbiome with a marked effect on the levels of Lactobacillus and Enterococcus. qPCR analysis of 46 host immune response genes did not detect significant differences in host gene expression between SC5134 and CHN1 colonized mice, except for chitinase expression. Thus, these studies suggest that yeast-bacteria interactions in the microbiome may be far more important in determining long-term colonization potential of C. albicans and secondary immunomodulatory effects.